Report of the Hospital Sub-committee - Horder, Thomas, 1871-1955 (London : Institutional Management Association)
1943-09-11 1943 1940s 15 pages 3. Public Rooms. Public rooms receive very hard wear and tear. It is advisable to have well built furniture in them and strong hard wearing floor coverings and soft furnishings. Walls and paint should be attractively coloured to harmonize with the soft furnishings. All table tops, writing tables, etc., should have a protective covering of plate glass or stain resisting finish. 4. Furniture and Fittings. i. Domestic Administrator's Sitting Room. Rug or Carpet Telephones Armchair Curtains (internal & external) 2 Occasional chairs Table Bookcase Waste-paper basket Bureau with Cupboard Fire, electric or gas ii. Domestic Administrator's and Assistant Domestic Administrator's Offices. Lock-up desk and com- Rug Telephone fortable chair Waste-paper basket (internal & external) 3 suitable office chairs Table Filing Cabinet Fire, electric or gas Bookcase & cupboard Typewriter iii. Sitting Rooms—Trained Staff and for Maids. Large Table Rugs or carpet Hand sewing machines Nest of small tables Cupboard for china Table Tennis Writing tables & chairs Bookcase Waste-paper basket Occasional chairs Wireless Library Settee and comfortable Piano Curtains chairs Fire, electric or gas Pictures and Mirror Cushions iv. Recreation Rooms. Where possible a combined recreation and lecture room is very desirable with:— Ping-Pong Table Wireless Floor suitable for Darts Board Tables and chairs dancing Piano (nesting) Movable blackboard Stage v. Maids' Dining Room. Tables with heat re- Chairs Hot cupboard sisting covering Suitable floor covering Service Counter with Cafeteria vi. Visitors' Room, for visitors to staff, furnished as a Sitting Room. vii. Bedrooms, Domestic Administrator, Assistant Domestic Administrator, and Trained Staff. Divan bed Wardrobe built-in, of sufficient height to take long dresses, and broad enough to take hangers on a central rod, with long mirror on inside door. Hat cupboard built-in Soiled linen receptacle Built-in wash basins with over wardrobe Chest of drawers com- opaline shelf, towel Boot cupboard or rack bined with desk rail, etc. Small cup- Arm - and - occasional Book shelf board with mirror in- chair Waste-paper basket side cupboard door Rug Bedside table above Curtains 12 292/842/2/104